2021
DOI: 10.31246/mjn-2020-0086
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the prevalence of hypertension and factors associated with blood pressure among hospitalised elderly in Hospital Serdang, Selangor, Malaysia

Abstract: Introduction: Increasing trends of hypertension has been recognised as a common disease among the elderly. This study aimed to determine the prevalence of hypertension and factors associated with blood pressure among hospitalised elderly. Methods: This was a cross-sectional study involving 124 patients in Hospital Serdang, Selangor, Malaysia. Data on socio-demography, medical background, anthropometry, blood biochemistry and lifestyle were collected through face-to-face interviews and medical records. Dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
0
2
Order By: Relevance
“…It has been revealed that the prevalence of diabetes and hypertension was higher (60%) in patients with higher body fat percentage and visceral fat levels (8). Additionally, in previous studies, the prevalence of hypertension in hospitalized elderly increased along with the number of overweight or obese individuals (25)(26)(27). Contrary to current study, a previous study found an association between presence of multimorbidity and body fat percentage, revealing that subjects suffering more than six comorbid conditions have a higher body fat percentage than those with the least chronic conditions (28).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…It has been revealed that the prevalence of diabetes and hypertension was higher (60%) in patients with higher body fat percentage and visceral fat levels (8). Additionally, in previous studies, the prevalence of hypertension in hospitalized elderly increased along with the number of overweight or obese individuals (25)(26)(27). Contrary to current study, a previous study found an association between presence of multimorbidity and body fat percentage, revealing that subjects suffering more than six comorbid conditions have a higher body fat percentage than those with the least chronic conditions (28).…”
Section: Discussioncontrasting
confidence: 96%
“…In terms of adequacy, most subjects did not meet energy and protein adequacy. The complaints were similar to previous studies in which subjects complained of no appetite, difficulty chewing and swallowing food, food was unappealing, and circumstances of their meals might have contributed to the insufficient intakes (25,47).…”
Section: Discussionsupporting
confidence: 88%
“…Besides, having a low energy intake also caused the body to catabolize muscles to produce energy to meet the daily need to carry out basic daily activities. Inadequacy of energy and protein intake as found in this study is common among hospitalized elderly in Malaysia (45,46). Thus, a previous study had also found that energy and protein inadequacy affected handgrip strength contradicting the current study finding (47).…”
Section: Discussioncontrasting
confidence: 79%